Customizable self-powered pressure sensor based on piezo-transmittance of tilted structures. (May 2023) - Wu, Lei; Ahn, Junseong; Choi, Jungrak; Gu, Jimin; Li, Xuan; Gul, Osman; Zhao, Zhi-Jun; Qian, Linmao; Yu, Bingjun; Park, Inkyu
Abstract: In the era of the Internet of Things, there is an increasing demand for specialized self-powered sensors owing to extensive applications involving an enormous number of distributed devices in numerous fields. However, realizing self-powered sensors with excellent predictability and designability to accommodate diverse application requirements remains a significant challenge because of the randomness of the nanomaterials or micro/nano-porous structures used. This report describes the development of a customizable and designable self-powered pressure sensor based on the piezo-transmittance of opaque tilted structures. The light transmittance decreases with increasing pressure owing to the deformation of tilted structures. Piezo-transmittance sensors with various linear ranges were customized by rationally designing Young's moduli and structural parameters and optimizing cross-sectional architectures of tilted structures. The pressure sensor was fabricated by molding on 3D-printed master patterns comprising various tilted structures. Each customized sensor exhibits excellent static and dynamic responses, and responses are unaffected by light intensity, ambient temperature, and humidity. Finally, the piezo-transmittance sensors were applied to a self-powered wireless breath monitoring system that integrated flexible solar cell and Bluetooth Low Energy, an all-weather wind detection system with simultaneous signal processing and energy harvesting, and a real-time control system for teleoperated a robotic manipulation. Graphical Abstract: This study developed a self-powered pressure sensor with excellent designability and customizability, leveraging the piezo-transmittance of opaque tilted structures. Moreover, we applied the piezo-transmittance pressure sensors with customized performances in a self-powered wireless breath monitoring system, an all-weather wind detection system with simultaneous signal processing and energy harvesting, and a real-time control system for teleoperated robot manipulation. ga1 Highlights: A piezo-transmittance based customizable self-powered pressure sensor was developed. Piezo-transmittance pressure sensors with various linear ranges were customized. Each customized sensor exhibits excellent static and dynamic responses. Sensor responses are unaffected by light intensity, ambient temperature, and humidity. The customized sensors were respectively applied in breath monitoring, wind detection, and robotic manipulation.